Fuzzy Logic Controller (FLC) for the control of Particulate Matter (PM) emission in wet scrubber system - Umar, Samba A.; Babawuro, Adamu Y.; Sado, Fatai; Salami, Momoh Jimoh Eyiomika; Khan, Md. Raisuddin (2015)
Air pollution such as particulate matter (PM) emitted from industries result in several thousands of deaths. In recognition of this global threat, a large number of abatement measures have been taken to minimize the emission of this pollutant. Wet scrubber system has been the most widely used control device for PM contaminants. Its operating variables (gas velocity, temperature profile, particle size, liquid droplet’s size, terminal settling velocity of liquid droplets, particle density and liquid to gas ratio) fluctuates randomly, thus resulting in a non-linear dynamic behavior of the system. This non-linearity generally limits the ability of the scrubber to control PM less than 5μm in diameter. Thus, in this study, intelligent control technique based on fuzzy logic controller (FLC) has been developed to solve the non-linearity in the system by selecting appropriate scrubbing liquid droplet size in order to improve system performance to control PM that are less than 5μm in diameter. The developed FLC has two inputs (error and change in error) and a single output. The results shows that within short settling time, the controller was able to effectively reduce the PM that are less than 5μm below the set-point (20μg/m3) which is the maximum allowable emission limit of PM contaminants by world health organization (WHO).